Foliar epidermal micromorphology of genus Glochidion J.R.Forst. & G.Forst. (Phyllanthaceae) by using light and electron microscopy - Brahma, Priyanka; Baruah, Sanjib (Current Botany, 2024)
The present study was conducted to compare both qualitative and quantitative characteristics of foliar epidermal micromorphology on some members of Glochidion in Assam. As taxonomic attributes, the foliar epidermal micromorphology study of nine taxa of both abaxial and adaxial surfaces was performed by using light microscopy (LM) and field emission scanning electron microscopy (FESEM). The result showed both amphistomatic and hypostomatic types of leaf surfaces. On the same surface of the leaf, multiple types of stomata were observed such as anomocytic, anisocytic, hemiparacytic, and paracytic types. Significant diversity and variations were observed in stomatal number, size, area, epidermal cell number, subsidiary cells, and trichomes. The stomatal index, stomatal shape, epidermal cell shape, length and width of the stomata, and trichomes showed variation among the studied taxa. Glands were absent in all studied members. Papillae and epicuticular wax crystals were observed in some taxa. In addition, a taxonomic key was also provided based on foliar leaf epidermal characteristics using qualitative and quantitative data from LM and FESEM. Based on quantitative data of foliar leaf micromorphology, principal component analysis (PCA) and cluster analysis were carried out to authenticate the micromorphological data. These would aid in the identification of taxa as well as in taxonomic delimitation.